Analisis Jenis Kalimat Langsung Pada Kumpulan Naskah Drama Dalam Website Brain Academy Edisi Maret 2024 Sebagai Sumber Bacaan Siswa Kelas X SMA - Intan Amelia Toty; Fadilah Fauziah; Meisa Nuri Aisyah; Alayya Edistya Putriayu Dhiya; Hasbia Kunti Taqia; Asep Purwo Yudi Utomo; Norma Eralita (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Drama scripts are one of the learning materials for 10th grade high school students. A collection of drama scripts on an online platform can be a source of reading and teaching materials for students. This study aims to determine the types of direct sentences in a collection of drama scripts on the Brain Academy website as teaching materials for 10th grade high school. This research will analyze the types of direct sentences in a collection of drama scripts. The data source in this research comes from the Brain Academy website, with 10 drama scripts as the benchmark. This research uses a methodological approach in the form of a qualitative descriptive method and a theoretical approach in the form of syntax. Data collection in this research uses listening and note-taking techniques. The data analysis processing used in this article is the agih method with the basic technique for direct elements. The data presentation used in this article uses formal and informal data presentation in the form of tables, diagrams, and narratives. Based on the analysis, it was found that the most used sentence type in the ten drama scripts is declarative with 100 sentences, and the least used is interjective with 11 sentences. The interrogative sentences found amounted to 44 sentences, imperative sentences amounted to 12 sentences, and inappropriate sentences amounted to 52 sentences. So, the total amount of data is 219 sentences.